ChemInform Abstract: Direct Reductive Amination of 5‐Hydroxymethylfurfural with Primary/Secondary Amines via Ru‐Complex Catalyzed Hydrogenation. Issue 18 (May 2015) - Xu, Zhanwei; Yan, Peifang; Xu, Wenjuan; Jia, Songyan; Xia, Zhi; Chung, Benjamin; Zhang, Z. Conrad
Abstract A wide range of primary and secondary amines are used for the direct reductive amination of bio‐based 5‐hydroxymethylfurfural (I) using the complex dichlorobis(2, 9‐dimethyl‐1, 10‐phenanthroline)ruthenium(II) as efficient catalyst and H2 as reductant.